Research of the Effect of Two- speed AMT Shift Mode on Electric Vehicle Performance - Sun Bing; Xiong Huiyuan; Yu limin; Liu Yizhang (Jixie chuandong)
The power shift mode of best performance,fuel economy and the comprehensive shift mode which considering both performance and fuel economy of the two- speed AMT are built. A double shift mode based on the parameters of average acceleration and the acceleration square root is designed by using fuzzy control theory. On the basis of Matlab / simulink platform,the carload,AMT and shift modes are established. By simulating the battery electric bus FDG6601 EVG,a comprehensive comparison analysis of the four shift modes are carried out,the result shows that the comprehensive shift mode and double shift mode can give consideration to the performance of power and economy while the double shift mode is much better in comprehensive performance,compared to the comprehensive shift mode,the energy consumption reduced by 11. 1%,0 50 km / h acceleration time reduced by 2. 48%.